Power PTN security comprehensive evaluation based on power application - Lidan GAO; Fengjie SUN; Guojun LIU; Jianqi LI (Dianxin kexue)
Abstract:Traditional multi service transport network based on SDH has a low adaptability to the data service and flexibility.PTN technology which makes up the deficiency of the original SDH network is a good supplement to SDH network.According to the requirements of security performance in PTN equipment,the technology and theory of multi index comprehensive evaluation was studied by referring to the relevant standards,the key evaluation index of power PTN security performance test was put forward.Finally,the security performance of the three models was evaluated by using the analytic hierarchy process and fuzzy evaluation system,and the feasibility of the evaluation system was verified.